A comparison of objective, standardised parent-administered questionnaires to that of subjective screening practices for the early detection of developmentaal delay in at-risk infants - Silva, Melinda Lee E (My University, 2011)
Background The early identification of developmental disorders facilitates early intervention, improving childhood outcomes. Parent-administered questionnaires have been recommended for this purpose. The PEDS COMBINED, which includes the Parents Evaluation of Developmental Status (PEDS) and PEDS Developmental Milestones (PEDS:DM), and the Ages and Stages Questionnaire (ASQ) are parent-administered questionnaires with good psychometric properties. It has not been determined if they identify the same infants at-risk for developmental delays however. It is also not know how South African paediatricians monitor childhood development. Objective To compare the ASQ, PEDS COMBINED and South African paediatricians’ subjective assessment (PSA) of neonatal intensive care graduates at 6-months corrected age. To identify trends in developmental screening practices, including the knowledge and use of parentadministered screening tools, in a diverse group of paediatricans working in Gauteng, South Africa. Methods Developmental screening and referral practices of paediatricians were ascertained by analysis of a short questionnaire sent to participating paediatricians. Concordance between the questionnaires and PSA was determined using the kappa coefficient (κ) and Test of Symmetry (κ ≤ 0.4 indicating poor agreement; κ ≥ 0.75 indicating excellent agreement). Results Concordance between the ASQ and PEDS COMBINED was 90.7% (κ = 0.82, ρ = 0.05). The PSA showed poor concordance with both PEDS COMBINED and ASQ (κ = 0.28, ρ = 0.03 and κ= 0.26, ρ = 0.01 respectively). The ASQ and PEDS COMBINED identified 40% and 42% of the cohort with developmental concerns and the PSA identified 6%. Only 13% of paediatricians used specific guidelines for developmental assessment and none used, or could name any parent-administered questionnaire. Conclusion There is excellent agreement between the ASQ and PEDS COMBINED in identifying the same children with developmental concerns. Paediatricians identified significantly fewer infants and showed statistically significant poor agreement with both questionnaires. Most paediatricians in Gauteng, South Africa are not using standardized screening tools to detect developmental delay and have poor knowledge regarding these tools.
MSc (Med), Child Health Neurodevelopment, Faculty of Health Sciences, University of the Witwatersrand
Keywords: developmental screening; developmental delay; PEDS; PEDS:DM; PEDS COMBINED; ASQ; NICU infant; infant; paediatrician; South Africa